Assessing market price dynamics during the COVID-19 pandemic in Rwanda - Hirvonen, Kalle; Rosenbach, Gracie; Spielman, David J. (International Food Policy Research Institute, 2021)
The COVID-19 pandemic and the economic measures taken to prevent its spread led to a global recession in 2020 that was expected to cause significant increases in poverty and food insecurity in many countries. Households were expected to experience a “double whammy” of decreased incomes and rising food prices. This examines whether food prices rose in Rwanda since the COVID-19 pandemic began in early 2020. The main findings from this price analysis suggest the following. • Food prices did not significantly rise (or fall) during the COVID-19 pandemic in Rwanda. • Prices of staple foods (cereals and other starches) declined following the pandemic’s onset in March 2020, while the prices of pulses (the second largest food consumption group in Rwanda after staple foods) experienced a seasonal spike at the end of 2021, but returned to below pre-pandemic levels throughout 2021. • For most food groups, price trends in each province generally followed the national price trends during the pandemic, with the exception of poultry and eggs. • Nationally, prices of poultry and eggs declined after the beginning of the pandemic, but these prices vary significantly by province, with prices in the Northern Province remaining above pre-pandemic levels and prices in all other provinces falling since the pandemic, with prices in Kigali City falling the most. Overall, these results suggest that households in Rwanda were not hit by the “double whammy” of decreased incomes and rising food prices, since food prices remained stable Rather, they may instead have only suffered from decreased incomes. These findings suggest that continued efforts to expand Rwanda’s social protection programs are needed to boost household purchasing power and ensure that households are able to consume more – and more nutritious – foods.